Rancang Bangun Aplikasi Pencatatan Order Akta Notaris dan PPAT I Wayan Pastika - Ryan Suarantalla; Mohammad Taufan Asri Zaen; Yuliadi Yuliadi; Hanif Priabdul Aziz (STMIK Budi Darma, 2021)
Notary Office and PPAT I Wayan Pastika is one of the offices that offer services in the field of notary which is located at street Kebayan Number 11 Sumbawa Besar. Currently, administrative activities at the Notary's office and PPAT Wayan Pastika are still manual or not computerized, such as in recording and checking incoming and outgoing data. This is Research is needed to help the notary office and PPAT I Wayan Pastika in the data processing. This study aims to build an application for notary deed and PPAT order data recording, which was built using the waterfall method software design and data collection methods with interviews, observations, and literature studies. This application is built using the Laravel framework with the PHP programming language, and Java Script and Mysql database. The final result of this research is an application for notary deed order data recording and PPAT to assist office staff in processing data